Combined antioxidant formulation of ascorbic acid with resveratrol ameliorates isoproterenol-induced myocardial infarction in rats - Gao, Haichao; Wang, Hong; Han, Tingting; Huang, Xiansheng; Li, Shucheng; Wang, Xibing (Penerbit Universiti Kebangsaan Malaysia, 2022)
The current investigation was proposed to assess the effectiveness of the combination of resveratrol and ascorbic acid against Isoproterenol (ISO)-induced myocardial infarction in rats. The experimental model was divided into six groups (n = 6 in each group). Group I: control, Group 2: isoproterenol (ISO)-100 mg/kg b.wt, Group 3: ISO+Resveratrol (RES) (20 mg/kg b.wt) treated, Group 4: ISO+ Ascorbic acid (AA) (80 mg/kg b.wt) treated, Group 5: ISO+RES (20 mg/kg b.wt)+AA (80 mg/kg b.wt) treated and Group 6: RES (20 mg/kg b.wt)+ AA (80 mg/kg b.wt) alone treated. The study showed an increase in lipid peroxides and cardiac markers in the serum samples of experimental animals administered with ISO. Treatment with RES and AA individually and a combinational formulation brought a significant decrease in lipid peroxides and cardiac markers. They increased the level of enzymatic antioxidants and non-enzymatic antioxidant levels. Histopathological results showed the distortion of heart architecture among the experimental groups administered with ISO and significant recovery when treated with RES and AA individually and in their combination. The study presents the effective combination of RES and AA in combating ISO-induced myocardial infarction and protection against ROS-mediated oxidative stress.